فعالية الإرشاد الانتقائي‎ ‎في خفض مستوى عدوان ‏العلاقات لدى طلاب الجامعة - عيسي، دينا علي السعيد (جامعة المنصورة - كلية التربية, 2024)
هدف هذا البحث إلى التعرف على طبيعة العلاقة بين عدوان العلاقات وكلُ من صعوبات التنظيم الانفعالي والنرجسية، وكذلك التعرف على الفروق بين الجنسين في عدوان العلاقات، وفعالية البرنامج المقترح في خفض عدوان العلاقات لدى طلاب الجامعة. وتكونت عينة البحث من (300) طالبًا وطالبًة بالجامعة، وتم استخدام مقياس عدوان العلاقات إعداد (Clark,2017) ترجمة الباحثة، ومقياس صعوبات التنظيم الانفعالي إعداد (Bjureberg, et al. 2016 ترجمة وتقنين عادل سيد وآخرون، 2019) ومقياس النرجسية (إعداد الباحثة). وتوصلت النتائج إلى وجود علاقة ارتباطية موجبة بين عدوان العلاقات وكلُ من صعوبات التنظيم الانفعالي والنرجسية لدي طلاب الجامعة، وأظهرت النتائج أنه توجد فروق ذات دلالة إحصائية بين الجنسين في عدوان العلاقات لصالح الإناث، كما أظهرت النتائج فعالية البرنامج الإرشادي في خفض عدوان العلاقات واستمرار فاعليته في خفض عدوان العلاقات بعد توقفه في نهاية فترة المتابعة لدى طالبات الجامعة The aim of this research is to identify the nature of the relationship between relational aggression and both difficulties in emotional regulation and narcissism, as well as to identify differences between the genders in relational aggression, and the effectiveness of the proposed program in treating relational aggression among university students. The research sample consisted of (300) male and female students at the university, and the Relationship Aggression Scale prepared by (Clark, 2017) (translated by the researcher) was used, and the Difficulties in Emotional Regulation Scale prepared by (Bjureberg, et al., 2016) translated and codified by Adel Sayed et al., 2019) and the Scale Narcissism (prepared by the researcher). The results showed that there is a positive correlation between relational aggression and both difficulties in emotional regulation and narcissism among university students. The results showed that there are statistically significant differences between the gender in relational aggression in favor of females. The results also showed the effectiveness of the counseling program in reducing relational aggression and its continued effectiveness in reducing Relationship aggression after its cessation at the end of the follow-up period among university students.
Keywords: الإرشاد الانتقائي -- الصحة النفسية -- الشخصية العدوانية -- العلاقات الاجتماعية -- طلبة الجامعات